2019
DOI: 10.1098/rsfs.2019.0067
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenoids enhance the stability of fatty acid membranes at the emergence of life potentially leading to an early lipid divide

Abstract: Two key problems concern cell membranes during the emergence and early evolution of life: what was their initial composition, and why did the membranes of archaea and bacteria diverge? The composition of the first cell membranes could shed light on the most likely environment for the emergence of life. The opposing stereochemistry of modern lipid glycerol-phosphate headgroups in bacteria and archaea suggests that early membranes were composed of single chain amphiphiles, perhaps both fatty acids and isoprenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 64 publications
(101 reference statements)
2
33
0
Order By: Relevance
“…The concentration-dependence of [4Fe4S] cluster assembly on cysteine concentration and its tight correlation with the signature absorbance shoulder at 420 nm, suggests that other types of cluster were indeed masked by the presence of [4Fe4S] clusters. We therefore used room temperature 57 Fe Mössbauer spectroscopy to determine the proportions of individual species present 34 . The samples were prepared by lyophilization (see the 'Methods' section) as our initial preparations of N 2 -dried samples did not produce normal UV-Vis traces when reconstituted (unlike our lyophilized samples).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration-dependence of [4Fe4S] cluster assembly on cysteine concentration and its tight correlation with the signature absorbance shoulder at 420 nm, suggests that other types of cluster were indeed masked by the presence of [4Fe4S] clusters. We therefore used room temperature 57 Fe Mössbauer spectroscopy to determine the proportions of individual species present 34 . The samples were prepared by lyophilization (see the 'Methods' section) as our initial preparations of N 2 -dried samples did not produce normal UV-Vis traces when reconstituted (unlike our lyophilized samples).…”
Section: Resultsmentioning
confidence: 99%
“…11). Attempts to characterise these samples further using 57 Fe Mössbauer spectroscopy were hindered by the fragility of the samples during sample preparation. After lyophilisation, samples were brittle with a floss-like structure making it impossible to transfer to Mössbauer sample holders.…”
Section: Resultsmentioning
confidence: 99%
“…If that were the case, then the topology of protocells would be correct (figure 2 d ). We have previously shown that vesicles formed from single-chain amphiphiles such as fatty acids and fatty alcohols are stable at pH 11 and above [92,93], so the scheme depicted in figure 2 d is feasible. The major question that we explore now is whether suitably steep H + gradients could develop across inorganic barriers containing disordered Fe(Ni)S minerals, which could ultimately promote the reduction of CO 2 by H 2 .…”
Section: Vectorial Electrochemistry At the Origin Of Lifementioning
confidence: 99%
“…Nevertheless, it is worth noting that most of these studies have commonly used one type of amphiphilic molecule in order to assemble such vesicles. For instance, recent work shows that using mixtures of amphiphiles of differing tail lengths (Jordan et al 2019b), or the addition of other types of amphiphiles such as isoprenoids (Jordan et al 2019a)-a more realistic simulation of the 'dirty chemistry' world of prebiotic chemistry-can yield vesicles which are significantly more resistant to higher salinity and pH values. In any case, such land-water interface sites which are characterized by fluctuating fresh water hydrothermal pools could also support other reactions.…”
Section: The Emergence Of Life: In the Oceans Or On Oceanic Edges?mentioning
confidence: 99%